Factores de riesgo del síndrome de dismovilidad en adultos mayores del hogar Daniel Álvarez Sánchez - Quiroga Ortiz, Nelly Yolanda (2015)
This research aims to determine the risk factors for the syndrome immobility, identify the degree of independence to perform basic activities of daily life, the degree of immobility, and the most frequent comorbidities to build a proposed intervention in Senior’s home ¨Daniel Álvarez Sánchez¨ of the city of Loja. Corresponding to a study qualitative and quantitative, descriptive, transverse and nonrandom with methodological application of the interview, functional evaluation and medical records grouped in a data collection sheet applied to fifty elderly. With the following results : risk factors correspond to 88 % hearing impairment , visual disturbances 86 % , previous falls 86 % , and difficulty balancing 60 % , 60 % depression, lack of physical activity 46 % , overweight 28% , malnutrition 8%, dysthymia 4% and obesity 2% . With regard to the degree of immobility the presence of a secondary sedentary life style to difficulty it stands to move 60%, 24% moved without the need for support and sedentary unrestricted 8% , plus mild dependence occurs in 38% , modern 20 % and 16 % have need of serious assistance to perform basic activities of daily living in the elderly, among the most common coexisting conditions they are : urinary incontinence 24 % , hypertension 20 % , 19% osteoarthritis , hypothyroidism and senile dementia prevalence equal 7%. The proposal is for intervention and educational activities that encourage motor skills. KEY WORDS: Elderly, Dismovilidad, Risk Factors.